UJI AKTIVITAS ANTIBAKTERI FRAKSI ETIL ASETAT KULIT BUAH MANGGIS (Garcinia mangostana Linn) TERHADAP Escherichia coli SECARA IN VITRO - ., Eko Saputro (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Infectious disease is one of the public health problems in developing countries such as Indonesia. Escherichia coli (E. coli) are themost common etiology of urinary tract infections, diarrhea, pyogenicinfections and septicemia. Mangosteen (Garcinia mangostana Linn.) isone of well known tropical fruit in Indonesia. Previous studies found thatthere were antibacterial activities of mangosteen peel. There is a fewstudy antibacterial potential of mangosteen, especially in fraction form.Therefore, it is necessary to find more informations of this study.Objective: This research aims to find know chemical compounds andantibacterial activity of ethyl acetate fraction of mangosteen peel (Garciniamangostana L.) and its effective inhibitory concentration against thegrowth of Escherichia coli. Method: Mangosteen peel was extracted bymaceration using methanol. This extracts was fractionated using ethylacetate. Its chemical compounds were determined by phytochemicalscreening. Antibacterial activity of ethyl acetate fraction tested with cupplate technique. Ciprofloxacin 5Âµg/15Âµl was used as positive control whileDMSO 10% was used as negative control. Result: Ethyl acetate fractioncontains alkaloid, tannin, saponin, flavonoid and terpenoid. Ethyl acetatefraction showed an antibacterial activity against Escherichia coli and itsactivities increased after 48 hours incubation. The effective inhibitoryconcentration against the growth of Escherichia coli was 5%. Conclusion:Ethyl acetate fraction of mangosteen peel has antibacterial activity againstEscherichia coli as bactericides. Keywords: antibacterial, ethyl acetate fraction of mangosteen peel,Escherichia coli